Algunos conocimientos compartidos de mujeres usuarias de centros de salud acerca del consumo de drogas - Enríquez Bielma, José Fernando (2022)
Objective: to describe the knowledge shared by women who use health-care centers in situations related to drugs and their consumption. Methodology: non- experimental, transverse, exploratory and qualitative research, with a cognitive anthropological approach was carried out from June 26 to April 28 2007, The sample was made up of 180 women who requested attention in any of the six urban health-care centers of the secretary of health of the city of Leon in the state of Guanajuato, Mexico. Results: A little more than 7 out of 10 replied that they knew drug consumers; 19 different meanings were found for the term 'drug consumers'. Conclusion: the results show a contrast with the knowledge possessed by some under-age groups